2022
DOI: 10.3390/brainsci12121597
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in Autism Spectrum Disorder: Clinical Characteristics and the Role of the Family

Abstract: Background: Anxiety Disorder (AD) is among the most common psychiatric comorbidity in children and adolescents with Autism Spectrum Disorder (ASD). Likewise, parental psychological distress (PPD) was linked to anxiety symptoms in children and adolescents with ASD. The aim of this study was to characterise, in a sample of children and adolescents with ASD, anxiety symptoms, the functional impairment associated and the presence of PPD. Methods: Participants were divided into three groups based on their diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Research indicates that these deficiencies result in sleep disorders and disrupted psychomotor, social, and verbal skills (Galli et al, 2022;Sasa et al, 2003;Yoshimura et al, 2020), all traits associated with ASD. These observations explain the use of R-TBHP and folic acid as treatments to improve Anxiety and sleep disorder in ASD are related to disturbed dopamine synthesis Anxiety (Guerrera et al, 2022;van Steensel et al, 2011) and sleep disorders (Devnani & Hegde, 2015) are two of the most common comorbidities associated with ASD. Research has shown that the dopaminergic system is involved in anxiety disorder (Dong et al, 2020) and in the regulation of the sleep cycle (Oishi & Lazarus, 2017).…”
Section: Folate Deficiency Is Linked To Autistic Characteristicsmentioning
confidence: 86%
See 1 more Smart Citation
“…Research indicates that these deficiencies result in sleep disorders and disrupted psychomotor, social, and verbal skills (Galli et al, 2022;Sasa et al, 2003;Yoshimura et al, 2020), all traits associated with ASD. These observations explain the use of R-TBHP and folic acid as treatments to improve Anxiety and sleep disorder in ASD are related to disturbed dopamine synthesis Anxiety (Guerrera et al, 2022;van Steensel et al, 2011) and sleep disorders (Devnani & Hegde, 2015) are two of the most common comorbidities associated with ASD. Research has shown that the dopaminergic system is involved in anxiety disorder (Dong et al, 2020) and in the regulation of the sleep cycle (Oishi & Lazarus, 2017).…”
Section: Folate Deficiency Is Linked To Autistic Characteristicsmentioning
confidence: 86%
“…Anxiety (Guerrera et al, 2022; van Steensel et al, 2011) and sleep disorders (Devnani & Hegde, 2015) are two of the most common comorbidities associated with ASD. Research has shown that the dopaminergic system is involved in anxiety disorder (Dong et al, 2020) and in the regulation of the sleep cycle (Oishi & Lazarus, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, PD may sometimes be characterized by frantic attempts to maintain relationships in terms of not being abandoned by their significant other (e.g., a boyfriend). Such a pattern of what looks like separation anxiety often characterizes individuals with ASD [ 19 , 55 ] due to, for example, a lifelong and natural dependency on a parental figure who is the only person capable of interpreting the person’s autistic communication and needs [ 56 , 57 , 58 ]. This is often the case for mothers who naturally adapt to their child’s needs throughout upbringing while compensating for other people’s lack of understanding.…”
Section: Interpersonal Functioningmentioning
confidence: 99%